Aerosol‐Cloud Interactions in Trade Wind Cumulus Clouds and the Role of Vertical Wind Shear. Issue 22 (24th November 2019) - Yamaguchi, Takanobu; Feingold, Graham; Kazil, Jan
Abstract: In shallow cumulus clouds, cloud deepening as a dynamical response to increased droplet number concentration has recently been shown to buffer the microphysical suppression of precipitation. In the current study, large eddy simulations with a two‐moment bin microphysics model are employed to revisit this buffering and to investigate the role of vertical wind shear in aerosol‐cloud interactions in trade wind cumuli. An idealized case is developed based on ship measurements and corresponding reanalysis data over the Sulu Sea in the Philippines in September 2012. A quasi‐steady state is reached after roughly 25 – 35 hr for all six simulations performed (three different aerosol concentrations covering 35 – 230 cm −3, with/without vertical wind shear). All simulations show that the aerosol effect is buffered, to first order; increased aerosol results in deeper clouds, a reduced cloud fraction, and an increase in the shortwave cloud radiative effect. For the no‐shear cases, positive aerosol perturbations result in a small increase in surface precipitation, while the opposite is true in the presence of vertical wind shear because of muted deepening. Analysis shows competing influences of vertical wind shear; enhanced cloud clustering protects clouds from evaporation and entrainment while tilting of clouds enhances evaporation. In spite of the small responses of surface precipitation to very large changes in aerosol, cloud size and spatial distributions and charge/discharge precipitation cycles differ significantly, expressing changes in the pathways to surface precipitation and a dynamical buffering of the system. Key Points: Large‐eddy simulations show buffering of aerosol‐cloud interactions in trade cumulus Wind shear enhances evaporation by tilting clouds, but protects cloud cores via clustering Charge‐discharge cycles are correlated with cycles in the cloud size distribution